HUBUNGAN KELINCAHAN DENGAN KETERAMPILAN PASSING BAWAH ATLET BOLA VOLI MINI DI SDS ADI MULYA SEI. TESO DESA SUKAMAJU KECAMATAN SINGING HILIR - Paslan Paslan; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract, Based on observations and the observations by the author in the field on a mini volleyball athletes in SDS Adi Mulya Sei. Teso Desa Sukamaju District of Singingi Hilir, skills under passing not so good as the result of passing was not until keteman, the ball does not, and often missed at the time wanted to do passing under it, of many of these issues are more likely to be seen is often missed step to passing under. This is presumably because of agility, so that researchers want to conduct research on the relationship of agility with lunder passing skills of volleyball mini. This type of research is correlational whereas research sample are mini SDS volleyball athlete Adi Mulya of 20 people with a total sampling technique. The study took place in the field of SDS Adi Mulya Sei. Teso Desa Sukamaju while a study was conducted in September-October 2016. The data obtained from the test results shutlle run for agility and passing skills tests under volleyball. Data analysis using product moment correlation and Liliefors test for normality. After the data were analyzed were found rhitung 0.875> 0.602 rtabel, thus it can be concluded that